The WTO Dispute Settlement System 1995-2010: Some Descriptive Statistics - Henrik Horn; Louise Johannesson; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2011)
The Dispute Settlement (DS) system is a central feature of the World Trade Organization (WTO) Agreement. This compulsory and binding two-level mechanism for the adjudication of disputes between WTO Members is the most active among international courts. The functioning of the DS system has attractive research interest among both lawyers and economists. This paper reports some descriptive statistics of the working of the DS system based on the recently updated Horn and Mavroidis WTO Dispute Settlement Data Set. The data set covers all 426 WTO disputes initiated through the official filing of a Request for Consultations from January 1, 1995, until August 11, 2011, and for these disputes it includes events occurring until July 28, 2011. There are in total approximately 67 000 observations. Each dispute is followed through its legal life via the panel stage, the Appellate Body stage, through to the implementation stage. The paper provides information on fundamental aspects of the use of the DS system, such as: How active have the different countries been as complainants and as respondents? Which agreements and which provisions are most commonly cited? How are the adjudicating panels composed? How successful have the different participants been?
Keywords: F13; F53; O19; 330; WTO; Dispute Settlement; Developing Countries; Internationale Schiedsgerichtsbarkeit; Internationale Wirtschaftsorganisation; WTO-Regeln; Handelskonflikt; Entwicklungsländer; Welt